Rose Crunch Delight Unique Snack Experience With A Touch Of Roses Supports Science Learning For Grade IV - Bayu Septian Anuraga Bayu; Rohmah Khasanah; Sumarno (Schola, 2024)
This research was conducted at SD Negeri 2 Sumur, Tamansari District, Boyolali Regency. The subjects of this research were teachers and students of grade IV. This research aims to introduce and create a food product called Rose Crunch Delight, a snack made from rose flowers. The solution offered SDN 2 Sumur is one of the schools located near Cluntang Village. By carrying the theme of local wisdom, SDN 2 Sumur tries to create food innovations from rose flowers. This is also integrated with the learning of science and natural sciences material on plants, sources of life on earth about snack foods that will be used as the basic ingredients for making rose chips. The research method uses qualitative through learning activities with an edupreneurship spirit, namely a unique snack experience with a touch of roses. The results of this study indicate that the innovative product made by SDN 2 Sumur is Rose Crunch Delight. This part of the plant can be used as an innovative product in the form of Rose Crunch Delight (Rose Flower Chips). Increasing the creativity and innovation abilities of students through the Rose Crunch Delight product in the science subject. That Edupreneurship is very much needed and must continue to be developed in Educational Institutions in Indonesia, both formal and non-formal.